2017
DOI: 10.1590/s0102-053620170317
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic characteristics of tomato plant cultivar Santa Cruz Kada grafted on species of the genus Solanum

Abstract: In this study were evaluated gas exchanges, fruit production and fruit quality of tomato Santa Cruz Kada grafted onto different species of the genus Solanum, using two grafting methods. For the grafted tomato cultivation, the authors used a randomized complete block design, in a 8x2 factorial scheme, evaluating eight rootstocks: accessions of mini tomatos (0224-5, RVTC 57, RVTC 20 and 6889-50); wild tomato species Solanum habrochaites var. hirsutum (PI-127826); Solanum pennellii (LA716); Solanum sessiliflorum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
1
7
0
4
Order By: Relevance
“…The increased performance with the use of rootstock vigor validates the findings of Kyriacou et al (2017); Soare et al (2018) and Zeist et al (2017), who indicated that grafting onto vigorous rootstocks has been employed in open fields and under protected cultivation, where grafting positively influenced growth, yield and fruit. Similar results were found by Khah et…”
Section: Resultssupporting
confidence: 79%
“…The increased performance with the use of rootstock vigor validates the findings of Kyriacou et al (2017); Soare et al (2018) and Zeist et al (2017), who indicated that grafting onto vigorous rootstocks has been employed in open fields and under protected cultivation, where grafting positively influenced growth, yield and fruit. Similar results were found by Khah et…”
Section: Resultssupporting
confidence: 79%
“…Accordingly, among the studied rootstocks, 'Dynafort' (S. lycopersicum × S. pimpinellifolium) proved to have the lowest plant and vegetative biomass and related σ 2 E values, meaning that its tendency to reduce tomato plant growth was poorly affected by the scion cultivar. S. habrochaites is a highly vigorous species, adapted to thrive in a wide latitudinal distribution, showing characteristics promoting growth in grafted tomato [22,23]. On the other hand, S. pimpinellifolium is the closest wide relative to the cultivated tomato, and has been used to improve tomato resistance to several biotic stressors [24] or fruit quality traits [25].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have investigated physicalchemical (Akbudak et al, 2009) and yield traits of tomato (Graça et al, 2015;Zhang et al, 2015;Zeist et al, 2017), as well as the correlation and the correlation unfolding between them (Meena and Bahadur, 2015;Ali et al, 2017). However, there are few papers addressing the correlations between traits and path analysis on cherry tomatoes.…”
Section: Introductionmentioning
confidence: 99%